The 26th Congress of ICAS and 8th AIAA ATIO 2008
DOI: 10.2514/6.2008-8885
|View full text |Cite
|
Sign up to set email alerts
|

Human-in-the-Loop Evaluation of Ground-Based Automated Separation Assurance for NextGen

Abstract: This paper describes human-in-the-loop research at NASA Ames Research Center on service provider-based automated separation assurance for the Next Generation Air Transportation System (NextGen). Key human/automation integration aspects such as levels of automation and roles and responsibilities of automated separation management are investigated in the Airspace Operations Laboratory. A trilogy of part-task studies was designed to examine efficiency, safety, workload impact and acceptability of central aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 11 publications
0
35
0
Order By: Relevance
“…Conflicts detected with less than three minutes to LOS were not intended to be resolved by the trajectory-based separation assurance function. Even though the number of such occurrences may be excessive, their existence confirms the need for the tactical safety layer which was a primary subject of the research conducted in summer 2008 28 . In addition to simply counting separation violations, the separation distances were also analyzed.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Conflicts detected with less than three minutes to LOS were not intended to be resolved by the trajectory-based separation assurance function. Even though the number of such occurrences may be excessive, their existence confirms the need for the tactical safety layer which was a primary subject of the research conducted in summer 2008 28 . In addition to simply counting separation violations, the separation distances were also analyzed.…”
Section: Safetymentioning
confidence: 99%
“…A detailed report on this study will be compiled once the data analysis has been concluded. In Prevot et al, 2008 28 the design of the study and a few initial findings are presented.…”
Section: Follow-on Researchmentioning
confidence: 99%
“…33 The prototype generated acceptable and efficient trajectory changes and appeared feasible for accommodating the anticipated demand growth in the next 20 years.…”
Section: Present Research Contributions 1 Separation Assurancementioning
confidence: 99%
“…NextGen intends to automate specific air traffic roles and responsibilities in order to reduce controller workload and increase their capacity to handle more aircraft. Tasks that are under consideration for automation in NextGen include conflict detection and conflict resolution [2]. In addition, tools and technologies are being considered to provide controllers with the capability of making route modifications that can be uplinked directly to the flight deck [3].…”
Section: Introductionmentioning
confidence: 99%